An empty land? On population dynamics and ageing in a North European periphery - Malmberg, Gunnar (DEU, 2016)
Based on various empirical investigations, the paper examines the population trends in the peripheral areas of northern Sweden. Though the region has experienced a population decline over the last decades, the population is rather stable and several forces seem to counteract the trends of population decline. Though mobility is a salient feature of today's society, migration trends are not increasing and many people in the remote regions are tied to networks in their home regions. And since non-job related motives are less common also the peripheries may attract migrants. Further, population development is also influenced by temporary mobility, and what is here called the "second population" may be of great importance for the future of the northern peripheries. In conclusion, the most likely future population development for the northern periphery is still a slow and stable decline. Der Beitrag untersucht anhand verschiedener empirischer Studien die Tendenzen der demographischen Entwicklung in den peripheren Gebieten Nordschwedens. Obwohl im Verlauf der letzten Jahrzehnte in der Region ein Rückgang der Bevölkerung zu verzeichnen war, ist die Bevölkerung ziemlich stabil, und mehrere Faktoren scheinen den Tendenzen einer Bevölkerungsabnahme entgegenzuwirken. Mobilität ist zwar ein hervorstechendes Merkmal der heutigen Gesellschaft, aber die Migrationstendenzen nehmen nicht zu, und viele Menschen in den peripheren Regionen sind in die Netzwerke ihrer Heimatregionen eingebunden. Und da nicht-arbeitsplatzbezogene Motive selten sind, können auch die peripheren Regionen Migranten anziehen. Weiterhin wird die Bevölkerungsentwicklung auch von temporärer Mobilität beeinflusst, und das, was man hier als "Zweitbevölkerung" bezeichnet, kann für die Zukunft der nördlichen Peripherien von großer Bedeutung sein. Abschließend ist festzustellen, dass die wahrscheinlichste künftige Bevölkerungsentwicklung für die nördliche Peripherie immer noch eine langsame und stetige Bevölkerungsabnahme ist.